ChemInform Abstract: A Convenient One‐Pot Access to Phenanthridinones via Suzuki—Miyaura Cross‐Coupling Reaction. Issue 41 (19th September 2013) - Tanimoto, Kouichi; Nakagawa, Naomichi; Takeda, Kazutaka; Kirihata, Mitsunori; Tanimori, Shinji
Abstract o‐bromobenzoic acid methyl esters with o‐aminophenylboronic acids